Psychological Determinants of Investor Motivation in Social Media-Based Crowdfunding Projects: A Systematic Review - Popescul, Daniela; Radu, Laura Diana; Păvăloaia, Vasile Daniel; Georgescu, Mircea Radu (Frontiers in Psychology, 2020)
Background: Using the power of Internet, crowdfunding platforms are currently changing the traditional landscape of fundraising. Social media-based IT platforms in particular are bringing the creators of crowdfunding projects closer than ever to potential investors. A large variety of factors function as determinants of individuals’ intention to participate in crowdfunding and have an intertwined impact on funding as the ultimate project goal. Objectives: For a better understanding of investor behaviour in social media-based crowdfunding projects, this paper covers identifying, analysing, and classifying general and specific factors of investor motivation, based on the literature in the field.The main focus is the relationship between the affordances provided by social media-based crowdfunding platforms and the psychological determinants of investor motivation in innovative start-up projects. Methods: Using IEEE Explore, Clarivate Web of Science, ScienceDirect, and Scopus, we conducted a systematic review of the existing research on the emerging role of crowdfunding as a disruptive technology in financing the start-up innovative projects. The paper explores the main determinants of investor motivation and aims to streamline the success factors in crowdfunding campaigns. Results: A total of 1,216 publications were identified after searching the aforementioned databases and, upon refining the results, 515 articles were considered for the final sample. After reading the titles and abstracts, the sample was reduced to 78 articles that were read in-depth and synthesized in accordance with the defined research questions. The selected articles were clustered into three main categories: general studies, determinants of investor behaviour, and success factors. Conclusions: In the new global economy, crowdfunding platforms have become the nexus between the emerging creators of innovative products and services and the necessary funding sources. This connection is possible via a cumulative collection of contributions from multiple investors recruited from the audience of the selected platform, without time or space constraints. However, the determinants of the investment decision are very different in the case of social media-based crowdfunding platforms compared to determinants in the mainstream environment. This paper surveys these motivators and reveals how platform features can be used to persuade individuals to make a financial contribution towards the success of a project.